Building community resilience in mine impacted communities : a study on delivery of health services in Papua New Guinea : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Kuir-Ayius, Dora Dau (Massey University, 2016)
The purpose of this study was to explore the building of Community Resilience in mine-impacted communities in Papua New Guinea (PNG). The study aimed to establish the general relationship between community resilience, community capitals and the delivery of health services. It investigated the delivery of health services in three mining communities in PNG to see how these services contribute to or detract from the building of resilience. The study investigated relevant models of community resilience from the literature, and how the way policy functions in PNG can be related to these models. The study also developed a way of quantifying the impact of mining on health service delivery (through the use of community capitals) and the building of resilience in these communities. Furthermore, the thesis develops an indigenous, Melanesian-centric ‘Bilum Framework’ approach to resilience to create greater understanding of how resilience in the mining communities can be strengthened through improved access to health services. Three mining communities were selected as case studies, each representing a different stage of mining: (i) the beginning; (ii) the operational; and, (iii) post-mine closure. A mixed method approach comprising both quantitative and qualitative methods was used to collect data for this study. A survey questionnaire was designed to collect views of community members who accessed health services in their respective communities. Results from the survey questionnaire were converted to proxy indicators and led to the development of a Community Resilience Index (CRI) to provide a measure of resilience in each community. The qualitative research methods included document analysis, semi-structured interviews, and purposive observations. Document analysis was important in reviewing relevant policy documents and other literature to link theories to the experiences of the people while the latter methods contributed to describing people’s encounters in accessing health services. Analysis showed inconsistencies in the levels of resilience in these communities that varied with the stages of mining: both the beginning and post- mine closure stages demonstrated significantly lower levels of community resilience than the operational phase. Findings from the research indicated a lack of access to health services – a key influence in building resilience – is the result a range of factors including insufficient finances, weak sector governance, and the need for infrastructure and transport. The Bilum Framework is proposed as an approach that allows decision-makers to target assistance to strengthen and support specific community capitals and hence more effectively build community resilience in the mining communities in PNG.
Keywords: Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Health and medical services in society; Health services accessibility; Mining districts; Resilience; Papua New Guinea